Enhancing Collaborative Communication Strategies with Members of The Regional Representatives Council (DPRD) in Yogyakarta - Luthfi Afif Azzaenuri; Christina Rochayanti Rochayanti; Basuki Agus Suparno (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
This research aims to find a model of governance for collaborative communication between members of the secretariat and members of the Regional People's Representative Council (DPRD) of Yogyakarta Special Territory (DIY) in the implementation of legislative functions. The methods used are phenomenological methods with qualitative-descriptive research techniques. The research data are obtained from in-depth interviews, face-to-face interviews, the DIY regulatory manuscripts of the DPRD, and meetings relating to rigidity, Propemperda 2020, public hearings, and especially Tree of Mind 2024. These data were analyzed using four theories, namely, the relationship communication theory, the face negotiation theory, the boundary management theory, and the collaborative governance theory. The study obtained the results of 13 models of communication governance in five categories as well as a general model of collaborative communication. In the first category, the communication relationship between board members, fractional staff, and staff members of the secretariat department, four models were found. In the second category, that is, communication relations between council members and staff of the fraction, two models were discovered. The conclusion of this research is that the 13th model of communication governance is a portrait of a phenomenon that needs to be improved in the DIY DPRD environment so that the selection of a common model of collaborative communications governance can support the communication relations of the secretariat and the members of the DIY DPRD in carrying out legislative functions